Insertion of Cold Shock Gene From Escherichia Coli in Wheat Plants to Produce Drought Tolerant Properties - Rimpan, Takashi Reymond; Dwany, Naomi; Meyners, Geraldy John; Ayustin, Yohana Delvia; Irawati, Wahyu (Biotropika: Journal of Tropical Biology, 2022)
Drought is a threat that affects plant growth and development. Wheat crops are very sensitive to heat and drought stress during flowering and grain development, which negatively affects grain yield and quality. Wheat with drought tolerant properties is a genetically modified plant obtained by inserting a cold shock protein gene from Escherichia coli so that it can increase the ability of wheat to adapt to drought. This literature review aims to provide information about the role of cold shock protein gene insertion from Escherichia coli in wheat plants to produce drought tolerant traits. The results of the literature review showed that the CspA gene from Escherichia coli inserted into DNA could increase gene expression by changing the nucleotides in the DNA sequence to increase G+C. Gene insertion produces recombinant DNA with specific nucleotide changes. Nucleotide changes were carried out to increase the overall G+C amino acid content without changing the existing CspA and CspB protein sequences. These changes played an important role in helping wheat adapt to drought. The leaves on the transgenic wheat showed a decrease in the rate of water loss because the stomata in these plants closed faster than in the ordinary wheat so that the transgenic wheat became more drought tolerant.